The elements of conceptism in the Visions of Francisco de Quevedo - Lazarević, Jelena V. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
The objective of this paper is to explain the definition of conceptismo as a literary and social movement with its most relevant characteristics, illustrated in “The Visions” of Francisco de Quevedo, one of the key baroque authors of the Spanish literature, through analyzing the initial vision – The Last Judgment. This cycle was written between the years 1606 and 1623 in the Spanish monarchy, a country filled with contrasts and enormous social differences. In each of the five Visions, Quevedo criticizes the social situation and the prominent archetypes of the Spanish society. The piece was written implementing sharp language, enriched with metaphor, contrasts, hyperbole and caricatures wrapped in satire: expressed both in discrete and bold manners. These artistic choices give unique literary nuances to the literary text and help the reader easily imagine Quevedoʼs world. A world in which everything is possible, even the equal treatment of the rich and the poor, leastwise after death. Both an absolute conceptualist and a strong satirist, Francisco de Quevedo does not miss a single opportunity to highlight injustices and make fun of what he considers relevant in the social sphere, treating the physical as the most visible, while paying the greatest attention to the moral aspects. Through a comparative study of the corpus chosen for this paper, forming conclusions about the social status in the Kingdom of Spain is expected, as well as a better understanding of its illustration through the artistic and literary choices of the author. Due to the detailed descriptions of the human nature and behaviors, which can be seen as universal archetypes, Quevedo’s “Visions” maintain their relevance to this day, as well as capture the attention of the contemporary reader.
Keywords: Francisco de Quevedo; conceptismo; Visions; prose; satire